Improving Compliance with Statins in Patients with Peripheral Arterial Disease: A Quality Improvement Study - Agha, Riaz A. (Ann Med Surg (Lond), 2012)
Atherosclerosis is an inflammatory disease affecting medium sized arteries. The prevalence, health, and financial impact of the disease has made it a key target for public health and large scale intervention. The statin class of drugs improve morbidity and mortality for patients with peripheral arterial disease (PAD) through polymodal actions. This quality improvement study aimed to determine, and subsequently reduce, the percentage of patients with PAD discharged without statins. According to the Vascular Society of Great Britain and Ireland, and draft National Institute of Health and Clinical Excellence guidance, all patients undergoing major vascular procedures should be prescribed a statin. A baseline audit of patients with PAD under the care of the vascular team at our instituted was undertaken for the period Dec 2009–July 2010. Electronic discharge letters (EDLs) were analysed and compliance with statin prescription were recorded. A number of interventions aimed at improving compliance were then enacted and monitored through weekly PDSA cycles. Junior doctor leadership was key to identifying the problem and conceiving, implementing, and measuring changes. A second cycle was run, using similar data collection methods to the first, for the period August-October 2010. In the first cycle, EDLs pertaining to 113 patient admissions, involving 96 patients with PAD, were examined. Statins were not prescribed in 30.1%. In the second cycle, 86 patient admissions, involving 76 patients, were examined. Statins were not prescribed in 24.4%, representing an 18.9% decrease. Poorly compliant sub-groups included patients presenting with embolism or those for elective angioplasty.